THE EFFECT OF FOOT EXERCISES ON BLOOD FOOT SENSITIVITY AND GLUCOSE LEVELS PATIENTS WITH TYPE 2 DIABETES MELLITUS: CASE SEPORT - Sita Irnadianis; Annas Sumeru (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
Introduction: Diabetes mellitus (DM) is a chronic disease in the form of a metabolic disorder characterized by blood sugar that exceeds normal limits. DM can cause various complications, and the most common is peripheral neuropathy. Management of type 2 DM sufferers includes supporting treatment. Purpose: This case study aims to determine the effect of foot exercise on foot sensitivity and blood sugar levels. Methods: The given implementation is based on Evidence-Based Nursing (EBN) and foot exercises are nursing interventions that can be used. Foot exercise intervention is carried out for 15-20 minutes once a day. Foot sensitivity was measured using monofilament based on Northern Devon Healthcare (2014) and blood glucose levels using Easy Touch GCU. Results were evaluated by monitoring foot sensitivity and blood sugar levels measured before and after the procedure for 6 consecutive days. Conclusion: There was a change in sensitivity and blood sugar levels after the foot exercise intervention was given.